Management and Control Strategy for Water Pollutant Discharge from Key Industries in the River Basin - LING Yaozhong; HAN Nini; PENG Xiang; WANG Chunling (Renmin Zhujiang)
The pollution is in the water while the source is on the shore.The pollutants in a river mainly come from the discharged onshore industrial and domestic sewage.Among them,the pollutants in the industrial wastewater from industrial enterprises have always been the difficulties in the environmental management of a river basin due to their large quantity,wide distribution,and complex types.Taking the electronics manufacturing industry,a key industry in the Shima River (Dongguan section) Basin,as a pilot,this paper puts forward a screening method for key industries in the basin from three aspects:the trend of regional development planning,the industrial economic structure of basin development,and the main pollution indicators.Then,it proposes a hierarchical evaluation standard system and differentiated management methods and further determines a management and control and risk prevention plan for water pollutant discharge from key industries in the basin to accumulate pilot experience for the supervision of industrial enterprises in the river basin.